LA RICHESSE ET LA DISTRIBUTION DES AMPHIBIENS DANS LA RÉGION DE SOUK AHRAS (NORD-EST DE L’ALGÉRIE) - TLIDJANE, A; MENAA, M; REBBAH, A. C; TELAILIA, S; SEDDIK, S; CHEFROUR, A; MAAZI, M.C. (My University, 2019)
Recently, global efforts towards biodiversity conservation have paid particular attention to Amphibia. Many amphibian species are threatened with extinction due to the loss or degradation of their habitats. Knowledge of the geographical distribution of amphibians in Algeria was until very recently relatively incomplete, but the book “Amphibians of North Africa” (ESCORIZA & BEN HASSINE, 2019) provides comprehensive distribution maps for all species, including those in Algeria. In order to improve knowledge of distributions, we conducted the first amphibian survey of the area of Souk Ahras region (north-eastern Algeria) by sampling at 102 sites between 2014 and 2017. Seven species were found, six of which are frogs (Hyla meridionalis, Bufo spinosus, Sclerophrys mauritanica, Bufotes boulengeri, Pelophylax saharicus and Discoglossus pictus) and one salamander (Pleurodeles nebulosus) which is a vulnerable Algero-Tunisian endemic. The species richness was higher (seven species) in the humid and sub-humid sites in the north of the Souk Ahras region than at the other sites; richness decreased progressively towards the semi-arid sites. Certain species showed a wide distribution, whereas others were very localized and rare, such as P. nebulosus, B. boulengeri and H. meridionalis